Analyzing Tourism Promotion and Service Tactics for Wanurejo Village’s Visitor Growth - Rosdiana, Anggita Cahya; Dwihantoro, Prihatin; Fitri, Shakira Insanu (Universitas Muhammadiyah Yogyakarta, 2023)
Tourism is a sector that can increase the amount of state revenue. This sector is used as an economic activity that accommodates many employment opportunities for the surrounding community, so as to increase income and community welfare. Like the Tourism Village in Borobudur, Magelang Regency, this tourism village develops several attractions in the form of natural tourism, cultural community activities and craft centers. This research targets to identify the situation of Wanurejo village tourism gadgets within the new everyday generation, secondly to find out the promoting strategy to growth the number of site visitors, thirdly to find out tourism offerings geared toward growing the wide variety of traveler traffic. This study makes use of descriptive-qualitative research whilst data series techniques use interviews, remark, and documentation. Wanurejo Tourism Village are several potentials such as tourism, arts, culinary, crafts, village events, and homestays. The result of the research obtained are that wanurejo village implements a promotion strategy in the new normal era using conventional and online strategies, social media and website are one of the media used in promoting wanurejo tourist village.